CRH promotes human colon cancer cell proliferation via IL‐6/JAK2/STAT3 signaling pathway and VEGF‐induced tumor angiogenesis. Issue 11 (13th July 2017) - Fang, Xianjun; Hong, Yali; Dai, Li; Qian, Yuanyuan; Zhu, Chao; Wu, Biao; Li, Shengnan
Abstract : Corticotrophin‐releasing hormone (CRH) has been demonstrated to participate in various diseases. Our previous study showed that its receptor CRHR1 mediated the development of colitis‐associated cancer in mouse model. However, the detailed mechanisms remain unclear. In this study, we explored the oncogenetic role of CRH/CRHR1 signaling in colon cancer cells. Cell proliferation and colony formation assays revealed that CRH contributed to cell proliferation. Moreover, tube formation assay showed that CRH‐treated colon cancer cell supernatant significantly promoted tube formation of human umbilical vein endothelial cells (HUVECs). And these effects could be reversed by the CRHR1 specific antagonist Antalarmin. Further investigation showed that CRH significantly upregulated the expressions of interlukin‐6 (IL‐6) and vascular endothelial growth factor (VEGF) through activating nuclear factor‐kappa B (NF‐κB). The CRH‐induced IL‐6 promoted phosphorylation of janus kinase 2 (JAK2) and signal transducers and activators of transcription 3 (STAT3). STAT3 inhibition by Stattic significantly inhibited the CRH‐induced cell proliferation. In addition, silence of VEGF resulted in declined tube formation induced by CRH. Taken together, CRH/CRHR1 signaling promoted human colon cancer cell proliferation via NF‐κB/IL‐6/JAK2/STAT3 signaling pathway and tumor angiogenesis via NF‐κB/VEGF signaling pathway. Our results provide evidence to support a critical role for the CRH/CRHR1 signaling in colon cancer progression and suggest its potential utility as a new therapeutic target for colon cancer.